"It's all about power and you have none:" The marginalization of tenant resistance to mixed-income social housing redevelopment in Toronto, Canada. (September 2016) - August, Martine
Abstract: Mixed-income redevelopment has become a go-to approach for restructuring post-war public housing in advanced capitalist nations. In Regent Park, Canada's first and largest project, revitalization is underway to create a mixed-use, mixed-income community — with rebuilt public housing, condos, and a redesigned landscape. While tenants face negative impacts related to relocation, displacement and gentrification, there has been a void of organized opposition to the project. This article tells the story of revitalization in Toronto and identifies five inter-connected factors that have worked as barriers to tenant organizing. These include: (1) a successful effort by the public housing authority to build support for revitalization by successfully branding it as tenant-driven, (2) a consultation process designed to limit collective interaction among tenants, (3) the co-optation of some critical voices, (4) fear of reprisal among tenants for speaking out, and (5) an internalized sense of powerless and un-deservingness among tenants. These factors have emerged in a context that does not foster resistance, as tenants are desperate for new housing, forced to come up against a popular revitalization approach, and suffering from attrition in numbers over a long development timeline. Despite these barriers to resistance, the limited opposition that has emerged in Toronto has been surprisingly successful, indicating the political potential tenants have to mount a fundamental challenge to mixed-income redevelopment, and to demand investment that is not tied to gentrification and displacement.